How to increase the effectiveness of your training: A tool kit of suggestions for trainers and speakers - Taylor, Harold L. (Bookboon, 2020)
Whether you are a public speaker, corporate trainer, freelance workshop leader, teacher or manager, there is something for you in this book. Harold explains why you should never ask “Are there any questions?” , why training modules should not exceed twenty minutes, why it’s important to know the group and the problems they are experiencing before the actual training, how the room environment can affect learning, why a variety of visual aids in essential, how to measure training results and more.